2008
DOI: 10.3928/1081597x-20081101-04
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Flap Adhesion Strength Using the Amadeus Microkeratome and the IntraLase iFS Femtosecond Laser in Rabbits

Abstract: <h4>PURPOSE</h4><p>To compare adhesion strength of flaps created with a mechanical microkeratome and the IntraLase femtosecond laser as well as to analyze the effect of different side-cut configurations.</p> <h4>METHODS</h4><p>A flap was created in four groups of New Zealand white rabbits—microkeratome group (Amadeus II microkeratome, Ziemer Group AG [5 eyes; 9-mm suction ring and 140-µm head]), and three IntraLase groups (IntraLase iFS 150 kHz femtosecond laser, AMO I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 9 publications
0
25
2
Order By: Relevance
“…In LASIK, the inverted side cut improves the strength of the healed wound. 36 The recipient side-cut angle was shallower than the donor. This minimizes the host side-cut depth to lessen the weakening of the host cornea.…”
Section: Discussionmentioning
confidence: 97%
“…In LASIK, the inverted side cut improves the strength of the healed wound. 36 The recipient side-cut angle was shallower than the donor. This minimizes the host side-cut depth to lessen the weakening of the host cornea.…”
Section: Discussionmentioning
confidence: 97%
“…Some studies showed that flap adhesion created with the femtosecond laser were stronger, and more uniform, regular and accurate than with the mechanical microkeratome 19 20. But there have also been reports of late traumatic flap complications, in the literature published in both English and Chinese 21 22.…”
Section: Discussionmentioning
confidence: 99%
“…It follows that there is less likelihood of producing flaps that threaten the biomechanical stability of the cornea or disrupt the epithelium when the femtosecond laser is used for LASIK. 27,56,57 Knorz and Vossmerbaeumer 58 evaluated and compared the adhesion strength of flaps created with a mechanical microkeratome and a femtosecond laser. They found that flap adhesion was stronger with a femtosecond laser flap.…”
Section: Corneal Ectasia and Biomechanicsmentioning
confidence: 99%
“…As discussed, femtosecond flaps have stronger adhesion than microkeratome flaps, 58 which may provide additional protection from the lower eyelid and inadvertent manipulations by the patient during the early postoperative period. When flap striae occur after LASIK performed with the femtosecond laser, management is similar to that with LASIK performed with the microkeratome.…”
Section: Striae and Foldsmentioning
confidence: 99%